Biomimetic erythrocyte-based drug delivery systems for organ-targeted therapy - Zhu, Kehui; Huang, Yike; Li, Keying; Zhang, Ke (Frontiers in Bioengineering and Biotechnology, 2025)
Enhancing drug accumulation in target organs while minimizing adverse effects is critical for pharmacological therapies. Therefore, the development of advanced drug-targeting platforms is essential for clinical application. These systems must not only enable precise organ-specific targeting but also improve drug bioavailability and extend systemic circulation. In recent years, significant progress has been made in blood cell-inspired drug delivery strategies, with red blood cells-based (RBCs-based) platforms showing particular promise due to their inherent physiological advantages. Nevertheless, the development of organ-specific RBCs-mediated delivery systems remains challenging. We categorize and summarize various drug loading methods for existing RBCs, along with their advantages, disadvantages, and treated disease types. We then focus on describing various design strategies of RBCs-based delivery systems targeting specific organs and review their current applications. Additionally, we discuss current challenges and future perspectives regarding RBCs-based targeted delivery platforms.